Explaining High Transport Costs within Malawi : Bad Roads or Lack of Trucking Competition? - Lall, Somik V. (2012)
What are the main determinants of transport costs: network access or competition among transport providers? The focus in the transport sector has often been on improving the coverage of "hard" infrastructure, whereas in reality the cost of transporting goods is quite sensitive to the extent of competition among transport providers and scale economies in the freight transport industry, creating monopolistic behavior and circular causation between lower transport costs and greater trade and traffic. This paper contributes to the discussion on transport costs in Malawi, providing fresh empirical evidence based on a specially commissioned survey of transport providers and spatial analysis of the country s infrastructure network. The main finding is that both infrastructure quality and market structure of the trucking industry are important contributors to regional differences in transport costs. The quality of the trunk road network is not a major constraint but differences in the quality of feeder roads connecting villages to the main road network have significant bearing on transport costs. And costs due to poor feeder roads are exacerbated by low volumes of trade between rural locations and market centers. With empty backhauls and journeys covering small distances, only a few transport service providers enter the market, charging disproportionately high prices to cover fixed costs and maximize markups.